Relationship of motivation with the determinants of job performance in remote work of workers at a public university in Peru - Panduro Riva, Claudia; Casas Huamanta, Edwin Roi (SATHIRI, 2022)
The purpose of this article is to identify the relationship between motivation and job performance in a remote work environment presented at a public university in Peru. Applying under a quantitative approach, of a descriptive type, of non-experimental, transectional and correlational design, with a sample of 54 people who perform remote work during the covid-19 pandemic, with a non-probabilistic and convenience sampling. Results: 52 % are women who perform remote work, 44 % are between 31 and 40 years old and 69 % have one year of work experience. 40 % present a medium work motivation; 43 %, extrinsic motivation; 48 % have low motivation. 41 % have low job performance; 39 %, average job performance; 52 %, average work behavior and 52 %, an average level of their work functions. Conclusions: There is a significant relationship between work motivation and work performance (p
Keywords: Work motivation; motivational cycle; work performance; remote work